Space Time Carving for Shape and Motion Recovery - Sakaue, Fumihiko; Takami, Masaaki; Sato, Jun (International Journal of Virtual Reality, 2010)
Recently, a lot of methods for shape and motion reconstruction have been studied extensively. This paper describes a method for simultaneous shape and motion reconstruction without any corresponding points. We call the method space-time carving. The proposed method is based on a space carving method which can reconstruct 3D shape without any corresponding points. The method uses photo-consistency for 3D space carving. Our proposed method also uses photo-consistency for carving high dimensional space which represents not only shape but also motion. As a result, the proposed method can recover not only 3D shapes but also 3D motions of objects. The experimental results show that the proposed method works well.